2013
DOI: 10.3184/175815513x13739879772128
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Monochromatic and Mixed LED Light Colour on the Behaviour and Fear Responses of Broiler Chicken

Abstract: This study observed the effect of different LED light colour on the behaviour and fear responses of broilers. In experiment 1, 400 broilers were placed into eight different light treatments. In experiment 2, six different light colours with five different age groups were considered. In experiment 1, use of a red and red-yellow mixed light significantly increased walking behaviour. Consequently, sitting and standing behaviour were found to be wavelength dependent, whereby short wavelength (blue, green-blue) tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
70
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(78 citation statements)
references
References 28 publications
8
70
0
Order By: Relevance
“…In our behavior observation trial, red and redyellow light activated the bird's movement and fear responses while blue and green-blue decreased the movement and they spent more time sitting , Prayitno et al, 1997 and thus impact on the welfare indicators (tibia dyschondroplasia, gait score) of broiler's (Sultana et al, 2016). However, we did not investigate the effect of different light colors on duck performance.…”
Section: Introductionmentioning
confidence: 83%
“…In our behavior observation trial, red and redyellow light activated the bird's movement and fear responses while blue and green-blue decreased the movement and they spent more time sitting , Prayitno et al, 1997 and thus impact on the welfare indicators (tibia dyschondroplasia, gait score) of broiler's (Sultana et al, 2016). However, we did not investigate the effect of different light colors on duck performance.…”
Section: Introductionmentioning
confidence: 83%
“…However, tibial BMD was not significantly influenced by light treatment in experiment 2. Thus, wavelength might influence BMD in birds, and our results indicate that Y light would increase BMD due to the increased physical activity of the broiler chicks (Sultana et al, 2013) and thus increased bone tissue development (Bizeray et al, 2000). On the other hand, several authors (Frost and Roland, 1991;Prayitno et al, 1997) reported that body weight is significantly correlated to both tibia breaking strength and bone density.…”
Section: Discussionmentioning
confidence: 99%
“…In follow up studies, serum GLU content was decreased under the B light treatment. Although the exact mechanism by which light color influences blood properties is unknown, it thought that the B light treatment calms the chickens (Prayitno et al, 1997), reduces anxiety (Sultana et al, 2013), and, thus, decreases blood pressure and serum glucose, HDL, and LDL levels. Consistent with the present results, Naveen et al (2006) conducted an experiment on humans and reported that B light significantly reduces breathing rate and diastolic blood pressure and that this mechanism may influence serum GLU and cholesterol concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…The color of monochromatic and mixed LEDs affects growth, development, and behavior in chickens (Rozenboim et al, 2004;Cao et al, 2008;Sultana et al, 2013). Changing the lighting regime to an LED system may impact not only growth and development but also immune function in broilers.…”
Section: Introductionmentioning
confidence: 99%